Synthesis of Adipic Acid via Eco-Friendly Oxidation of Cyclohexanone–Cyclohexanol Mixture over B₂O₃–SiO₂ Catalyst - Jonra P. Sitanggang; Alfan Wijaya; Risfidian Mohadi; Aldes Lesbani (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2025)
The synthesis of adipic acid through the oxidation of a cyclohexanone–cyclohexanol mixture was investigated using 30% hydrogen peroxide (H₂O₂) as the oxidizing agent and a B₂O₃–SiO₂ catalyst synthesized via heat treatment at various temperatures. This study aimed to evaluate the catalytic performance of B₂O₃–SiO₂ in facilitating the oxidation reaction and to determine the optimum reaction conditions for achieving the maximum yield of adipic acid. The effects of reaction time and temperature on the oxidation process were systematically studied. The reactions were conducted for 5, 6, 7, and 8 hours at temperatures of 60°C, 70°C, 80°C, and 90°C. The reaction products were analyzed using Gas Chromatography (GC) and Fourier Transform Infrared Spectroscopy (FT-IR). The results showed that the B₂O₃–SiO₂ catalyst exhibited the highest catalytic activity at 90°C, producing adipic acid with a maximum yield of 2.36% after 7 hours of reaction. Based on FT-IR characterization, it was observed that the B₂O₃–SiO₂ catalyst became unstable after the reaction, as indicated by the reduction of Brønsted acid sites. This decrease in acidity led to a less effective catalytic performance, resulting in a suboptimal oxidation process and a relatively low yield of adipic acid.